Periprosthetic knee infection: two stage revision surgery - Bonanzinga, Tommaso; Tanzi, Giuseppe; Iacono, Francesco; Ferrari, Matteo Carlo; Marcacci, Maurilio (Acta Biomedica Atenei Parmensis, 2017)
Periprosthetic joint infection (PJI) remains a serious complication following a total joint replacement. Diagnosis and management of PJI is challenging for surgeons since there is no “gold standard”. This challenging condition requires a coordinated management approach to achieve good patient outcomes. Further difficulties involve choosing the optimal method to treat the periprosthetic joint infection. In this article, it is stressed the role of the two-stage revision: implant removal, debridement and placement of an antibiotic spacer, and antibiotic therapy with cessation prior to reimplantation. Published literature shows that two stage revision is a valid treatment option for periprosthetic joint infection.